Three-dimensional porous ceramic as well as preparation method and application thereof
Through 3D printing technology and boron nitride surface treatment, ceramic composite materials with high dielectric constant were prepared, which solved the problems of structural design limitations, stress cracking after forming and interface defects in the prior art, and achieved high dielectric constant and excellent processing performance.
Patent Information
- Application Number
- CN202411975368.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing three-dimensional continuous dielectric ceramics preparation of high-dielectric constant ceramics/polymer composites have limited structural design, prone to stress cracking and interface defects after forming, resulting in reduced dielectric strength and complex process problems.
3D printing technology is used to combine microns and nano-scale dielectric ceramic particles with photosensitive resin to prepare an ordered functional ceramic skeleton, and the surface treatment of vacuum impregnation of resin and boron nitride is formed to form a ceramic composite material with high dielectric constant.
A ceramic composite material with high dielectric constant at a lower ceramic content is achieved, which improves dielectric strength and processing performance, simplifies the process flow, and enhances the bonding power between ceramics and polymer materials.
Smart Images

Figure HDA0005220321620000011 
Figure HDA0005220321620000012 
Figure HDA0005220321620000013
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a three-dimensional porous ceramic and a preparation method and application thereof. Background Art
[0002] As an efficient storage and conversion device for sustainable energy, dielectric capacitors are developing in the direction of miniaturization, lightness and high performance. High dielectric constant materials are the core of high energy storage dielectric capacitors and have received much attention in current research. The dielectric constant of polymers can be enhanced by adding dielectric ceramic particles to polymers. However, in order to obtain a high dielectric constant for ceramic / polymer composites, a large amount of ceramic particles (greater than 50 vol%) needs to be added, which will inevitably lead to a series of problems in the composite materials, such as deterioration of the molding process, increased leakage current, increased dielectric loss, and increased defects leading to reduced dielectric strength.
[0003] By constructing a three-dimensional dielectric ceramic network (foam ceramic, porous ceramic, etc.) to prepare a ceramic / polymer composite material, the performance and processability of the ceramic composite material can be optimized. For example, the prior art prepares a three-dimensional open-cell barium titanate (BT) foam ceramic / cyanate resin composite material and a three-dimensional porous BT network structure / epoxy resin composite material, and its dielectric constant reaches 141.3 (100Hz) (Journal of Materials Chemistry C, 2016, 4 (45): 10654-10663.), 200 (1kHz) (Energy & Environmental Science, 2017, 10 (1): 137-144.). This continuous ceramic skeleton exhibits dielectric properties different from those of traditional BT particle-filled polymer composites, and obtains a higher dielectric constant at the same or lower ceramic addition amount. Moreover, since the ceramic particles are pre-constructed into a continuous whole, the dispersion of the ceramic particles no longer needs to be considered during the composite material molding process, and it has good processability. However, the existing three-dimensional continuous dielectric ceramics for preparing high dielectric constant ceramic / polymer composites still have the following problems: (1) The structure of the existing three-dimensional ceramic network depends on the carrier of the ceramic particles. The carrier of these ceramic particles is the key to achieving a high-performance three-dimensional ceramic network structure, but it limits the design of the three-dimensional ceramic network structure; (2) After the ceramic skeleton is sintered, a relatively dense structure is formed, which has poor wettability with polymers, and defects are easily generated at the two-phase interface. After molding, stress cracking is easily caused to form defects. These defects will greatly reduce the dielectric strength of the final composite material; (3) The process of existing ceramic composite materials is complex and not easy to implement.
[0004] Chinese patent CN117447198B discloses a 3D printed barium titanate ceramic and its preparation method. After barium titanate powder is mixed with a photocurable resin system to form a slurry, the structure of the lead-free piezoelectric material is designed through a 3D printing process to prepare a piezoelectric material that is not environmentally harmful and has a controllable structure. Chinese patent application CN111032327A discloses a structured ceramic composite material that imitates natural materials and is made by cold sintering. The cold sintering method based on the open-porous matrix and the diversity of microstructures allow the manufacture of various single-layer and multi-layer cold-sintered ceramic composite materials with excellent strength, toughness and crack extension resistance. However, none of these prior arts solves the above technical problems.
[0005] In this context, there is an urgent need to provide a ceramic material with high dielectric strength, good processing performance and strong designability. Summary of the invention
[0006] The present invention provides a three-dimensional porous ceramic and a preparation method thereof, which fully utilizes the designability of 3D printing technology, designs an ordered three-dimensional spatial structure, uses photo-curing 3D printing technology to accurately design and prepare an ordered functional ceramic skeleton, further performs surface treatment on the ceramic skeleton, and then vacuum impregnates resin to grow boron nitride on the surface of the ceramic skeleton to obtain a ceramic composite material with a high dielectric constant.
[0007] The first aspect of the present invention provides a three-dimensional porous ceramic, the preparation raw materials of which include: photosensitive resin and dielectric ceramic particles; the weight ratio of the photosensitive resin to the dielectric ceramic particles is 1:(1.2-4).
[0008] Preferably, the dielectric ceramic particles include a first barium titanate and a second barium titanate; the particle size of the first barium titanate is 0.1-5 μm, and the particle size of the second barium titanate is 20-500 nm.
[0009] Preferably, the particle size of the first barium titanate is 0.5-2 μm, and the particle size of the second barium titanate is 50-200 nm.
[0010] Preferably, the mass ratio of the first barium titanate to the second barium titanate is 1:(2-5); more preferably 1:3.
[0011] Preferably, the addition amount of the dielectric ceramic particles in the three-dimensional porous ceramic is 50-80wt%, and more preferably 70wt%.
[0012] Preferably, in terms of weight percentage, the raw materials for preparing the photosensitive resin include 90-95% of resin monomer, 1-5% of leveling agent, 0.5-3% of viscosity regulator, and 0.5-2% of photoinitiator.
[0013] More preferably, in terms of weight percentage, the raw materials for preparing the photosensitive resin include 92.7% of resin monomer, 3% of leveling agent, 2.5% of viscosity regulator, and 1.8% of photoinitiator.
[0014] Preferably, the resin monomer includes one or more combinations of 1,6-ethylene glycol diacrylate (HDDA), trimethylolpropane triacrylate (TMPTA), 2-methyl-2-hydroxyethyl acrylate phosphate, methyl methacrylate (MMA), ethylene glycol dimethacrylate (EGDMA), isobornyl acrylate (IBOA), lauric acid methacrylate, and cyclotrimethylolpropane formal acrylate (CTFA).
[0015] More preferably, the resin monomers include 1,6-ethylene glycol diacrylate, trimethylolpropane triacrylate and 2-methyl-2-hydroxyethyl acrylate phosphate in a mass ratio of (50-70): (20-35): (0.5-5).
[0016] Preferably, the leveling agent includes polyether-modified polysiloxane, which may be BYK307.
[0017] Preferably, the viscosity modifier can be SA-6000.
[0018] The photoinitiator is a compound that can absorb energy of a certain wavelength in the ultraviolet or visible region to generate free radicals, cations, etc., thereby initiating polymerization, crosslinking and curing of monomers, and can be listed as free radical polymerization photoinitiators, cationic photoinitiators, etc.
[0019] Examples of free radical polymerization photoinitiators include, but are not limited to, TPO (phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide), 1173 (2-hydroxy-2-methyl-1-phenylpropanone), 184 (1-hydroxycyclohexylphenyl ketone), 907 (2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone), and BP (benzophenone).
[0020] Examples of cationic photoinitiators include, but are not limited to, diazonium salts, diaryliodonium salts, triarylsulfonium salts, alkylsulfonium salts, iron arene salts, sulfonyloxy ketones, triarylsiloxane ethers, etc. For example, 810 (diphenyliodonium hexafluorophosphate).
[0021] Preferably, the photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (commonly known as TPO).
[0022] The present invention proposes a new three-dimensional porous ceramic preparation technology, the core of which is to integrate micron and nanometer-scale dielectric ceramic particles into photosensitive resin to prepare a high-performance dielectric ceramic slurry. This innovation not only greatly enriches the preparation methods of ceramic materials, but also significantly improves the comprehensive performance of ceramic materials. In the specific implementation process, the present invention uses advanced photocuring 3D printing technology to accurately print the dielectric ceramic slurry with a preferred ratio into a three-dimensional ceramic skeleton green body. This process not only realizes the precise manufacturing of complex structures, but also greatly improves production efficiency and material utilization. Subsequently, through a high-temperature sintering process, the ceramic skeleton green body is converted into a functional ceramic skeleton, ensuring the high strength and excellent dielectric properties of the ceramic material. More preferably, after obtaining the functional ceramic skeleton, the present invention performs boron nitride surface treatment on it. This step not only makes the surface of the ceramic skeleton rough, increases the specific surface area and active sites of the surface, but also effectively improves the bonding force between the ceramic skeleton and the polymer material. This surface treatment technology not only broadens the application field of three-dimensional porous ceramics, but also provides a more solid foundation for its composite with polymer materials.
[0023] The second aspect of the present invention provides a method for preparing the three-dimensional porous ceramic as described above, wherein the preparation steps include:
[0024] S1. The photosensitive resin and the dielectric ceramic particles are mixed and ball-milled to obtain a dielectric ceramic slurry;
[0025] S2. 3D printing the dielectric ceramic slurry to obtain an ordered functional ceramic skeleton;
[0026] S3. Surface treatment is performed on the ordered functional ceramic skeleton to obtain a three-dimensional porous ceramic product.
[0027] The S2 step specifically includes:
[0028] S2.1 placing the dielectric ceramic slurry in a resin tank of a 3D printer and printing according to a set model to obtain a ceramic green body;
[0029] S2.2 The ceramic green body is sintered once to obtain an ordered functional ceramic skeleton.
[0030] Preferably, the ball milling time in step S1 is 1-3 h; more preferably 2 h.
[0031] Preferably, in step S2.1, the printing conditions are set as follows: the printing layer thickness is 10-50 μm, the single layer exposure time is 5-20 s, and the light curing energy is 2.1 mW / cm 2 .
[0032] Preferably, double hopper replacement printing is adopted in step S2.1.
[0033] Preferably, in the step S2.2, the conditions for the primary sintering are set as follows: placing the ceramic green body in a muffle furnace, heating it to 1100-1500° C. at a rate of 0.5-3° C. / min, and sintering it for 2-5 hours.
[0034] More preferably, the primary sintering temperature is 1250-1350°C; most preferably 1300°C.
[0035] Preferably, the step S3 specifically includes: immersing the ordered functional ceramic skeleton in a polyvinyl alcohol aqueous solution, taking it out and drying it, and performing secondary sintering to obtain a three-dimensional porous ceramic product. After the step S3, boron nitride grows on the surface of the ceramic skeleton, and the performance is further optimized.
[0036] Preferably, the polyvinyl alcohol aqueous solution contains 10-30 wt % of boron nitride.
[0037] Preferably, the drying temperature in step S3 is 50-70°C.
[0038] Preferably, the temperature of the secondary sintering in step S3 is 800-950° C., and the time of the secondary sintering is 1-4 hours.
[0039] A third aspect of the present invention provides an application of the three-dimensional porous ceramic as described above, wherein the three-dimensional porous ceramic is applied to technical fields such as electronic devices, medical equipment, communication equipment, aerospace, etc.; in particular, it is suitable for capacitors.
[0040] The present invention prepares ceramic / polymer composite materials by constructing a three-dimensional dielectric ceramic network, further selecting the polymer as a photosensitive resin, and coordinating it with 3D printing technology. It not only solves the problem of poor molding process caused by high ceramic addition, but also can obtain ceramic composite materials with high dielectric constant at a lower ceramic content. The obtained material has excellent electrical properties and broad application prospects.
[0041] Beneficial effects:
[0042] The present invention provides a three-dimensional porous ceramic and a preparation method thereof, which has the following advantages:
[0043] (1) The present invention uses two types of composite dielectric ceramic particles (micrometer-sized and nanometer-sized) in combination with a photosensitive resin to prepare a ceramic composite material with a high dielectric constant.
[0044] (2) The present invention innovatively adopts photocuring 3D printing technology to prepare a three-dimensional continuous dielectric ceramic skeleton, combined with a specific formula of photosensitive resin and sintering process, so that the ceramic skeleton structure is highly designable and can flexibly meet processing needs.
[0045] (3) The present invention performs surface treatment of boron nitride on the basis of a 3D-printed ceramic skeleton and regulates the conditions of secondary sintering so that boron nitride grows on the surface of the skeleton to form a two-dimensional material inlaid with rods and sheets, thereby giving the dielectric ceramic a rough surface structure.
[0046] (4) The three-dimensional porous ceramics obtained by the present invention have a rough surface, which can further form a strong bonding force with the polymer material, which is beneficial to enhance the interface between the ceramics and the polymer and meet the needs of downstream parts.
[0047] (5) The raw materials of the present invention are easily available, the processing technology is simple, and it is easy to implement; and the dielectric constant of the electrolyte composite material finally obtained reaches 170.3 (100 Hz), the dielectric loss is as low as 0.03, and the product quality is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 . SEM image of the ordered functional ceramic skeleton (without surface treatment) obtained in Example 1;
[0049] Figure 2 . SEM image of the three-dimensional porous ceramic skeleton obtained in Example 1;
[0050] Figure 3 . SEM image of the three-dimensional porous ceramic skeleton obtained in Example 2;
[0051] Figure 4 . A cross-sectional SEM image of the dielectric composite material obtained in Application Example 1;
[0052] Figure 5 . Cross-sectional SEM image of the dielectric composite material obtained in Application Example 2;
[0053] Figure 6 . Application Example 1: Dielectric constant and dielectric loss results of dielectric composite materials;
[0054] Figure 7 .Application Example 2: Dielectric constant and dielectric loss results of dielectric composite materials. DETAILED DESCRIPTION
[0055] The materials used in the examples of the present invention are all commercially available from the following sources.
[0056] Barium titanate (100 nm): Shanghai MacLean Biochemical Technology Co., Ltd.;
[0057] Barium titanate (1um): Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0058] Boron nitride (<200nm): Shanghai MacLean Biochemical Technology Co., Ltd.;
[0059] SA-6000: Sheng Armor Enterprise Co., Ltd.
[0060] 1,6-Ethylene glycol diacrylate: Sartomer (Guangzhou) Chemical Co., Ltd.;
[0061] Trimethylolpropane triacrylate, 2-methyl-2-hydroxyethyl acrylate phosphate: Shanghai MacLean Biochemical Technology Co., Ltd.;
[0062] Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide: IGM International Trading (Shanghai) Co., Ltd.;
[0063] BYK307: BYK Additives (Shanghai) Co., Ltd.
[0064] Polyvinyl alcohol: Sinopharm Chemical Reagent Co., Ltd.
[0065] Note: Unless otherwise specified, the solvents of the solutions involved in the present invention are all water; and the raw materials used are all commercially available.
[0066] Example
[0067] Example 1
[0068] This embodiment provides a three-dimensional porous ceramic and a preparation method thereof.
[0069] The raw materials for preparing the three-dimensional porous ceramic include: 60g of photosensitive resin and 135g of dielectric ceramic particles.
[0070] The dielectric ceramic particles include a first barium titanate and a second barium titanate; the particle size of the first barium titanate is 1 μm, the particle size of the second barium titanate is 100 nm, and the mass ratio of the first barium titanate to the second barium titanate is 1:3.
[0071] In terms of weight percentage, the raw materials for preparing the photosensitive resin include resin monomers (63% of 1,6-ethylene glycol diacrylate, 27.7% of trimethylolpropane triacrylate, 2% of 2-methyl-2-hydroxyethyl acrylate phosphate), 3% of leveling agent, 2.5% of viscosity regulator, and 1.8% of photoinitiator.
[0072] The leveling agent is BYK307.
[0073] The viscosity regulator is SA-6000.
[0074] The photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
[0075] The preparation steps of the three-dimensional porous ceramics include:
[0076] S1. Preparation of 3D printing slurry: In a light-proof condition, the raw materials of the photosensitive resin are mixed according to the formula amount to obtain a photosensitive resin mixed solution, dielectric ceramic particles are added thereto, and the mixture is ball-milled for 2 hours to obtain a dielectric ceramic slurry;
[0077] S2. 3D printing the dielectric ceramic slurry, specifically including:
[0078] S2.1 Place the dielectric ceramic slurry in the resin tank of the 3D printer (DLP 3D printer), and print according to the set model to obtain a ceramic green body; the printing conditions are set as follows: double tank replacement printing, printing layer thickness of 20μm, single layer exposure time of 10s, and light curing energy of 2.1mW / cm 2 .
[0079] S2.2 Place the ceramic green body in a muffle furnace, heat it to 1300°C at a rate of 1°C / min, and sinter it for 3 hours to obtain an ordered functional ceramic skeleton.
[0080] S3. Surface treatment: The ordered functional ceramic skeleton is immersed in a 5 wt % polyvinyl alcohol aqueous solution, taken out and dried in an oven at 60° C., and secondary sintered at 900° C. for 2 h to obtain a three-dimensional porous ceramic product.
[0081] Example 2
[0082] This embodiment provides a three-dimensional porous ceramic and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the temperature of the secondary sintering is 1100°C.
[0083] Application Example 1
[0084] This application example provides a dielectric composite material and a preparation method thereof. The three-dimensional porous ceramic product of 20*20*3mm prepared in Example 2 is placed in a mold, and a sufficient amount of epoxy resin solution (containing 10wt% triethylenetetramine) is added to fill the three-dimensional pores. The product is degassed in a vacuum oven for multiple times until no bubbles are generated. The product is then cured at room temperature for 24 hours, and then transferred to an oven at 100°C for 4 hours to obtain a dielectric composite material.
[0085] Application Example 2
[0086] This application example provides a dielectric composite material and a preparation method thereof. The ordered functional ceramic skeleton of 20*20*3mm obtained in step S2 of Example 2 is placed in a mold, and a sufficient amount of epoxy resin solution (containing 10wt% triethylenetetramine) is added to fill the three-dimensional pores. The product is degassed in a vacuum oven for multiple times until no bubbles are generated. The product is then cured at room temperature for 24 hours and transferred to an oven at 100°C for 4 hours to obtain a dielectric composite material. Cracks appear at the interface of the obtained product.
[0087] Application Example 3
[0088] This application example provides a dielectric composite material and a preparation method thereof, and the specific implementation method is the same as that of application example 1, except that: the amount of dielectric ceramic particles added to the three-dimensional porous ceramic is 65wt%. The dielectric constant of the final product is 14 (100Hz).
[0089] Performance Testing
[0090] 1. Sample morphology
[0091] The materials obtained in Examples 1 and 2 and Application Examples 1 and 2 were observed by SEM. Figures 1 to 5 .
[0092] contrast Figure 1 , Figure 2 It can be seen that a rough surface is formed after the 3D printed ceramic skeleton of the present invention is impregnated with boron nitride nanoparticles. Figure 2 , Figure 3 It shows that after sintering at 900℃ and 1100℃, the boron nitride particles accumulate and grow to form a two-dimensional material structure inlaid with rods and sheets. This structure constructs a rough surface morphology on the surface of dielectric ceramics. Figure 4 , Figure 5 It can be seen that the three-dimensional porous ceramics prepared in the present invention have good interface bonding with the resin, which is due to the rough structure of the surface of the three-dimensional porous ceramics.
[0093] 2. Dielectric properties
[0094] The dielectric constant and dielectric loss of the finished products of Application Examples 1 and 2 were measured using a broadband dielectric spectrometer (Novocontrol Concept 40). The results are shown in Figure 6 , Figure 7 .
[0095] like Figure 6 , Figure 7 As shown, the dielectric constant of the dielectric composite material finally prepared in Application Example 1 reaches 170.3 (100 Hz), and the dielectric loss is as low as 0.03, while the dielectric constant of the dielectric composite material finally prepared in Application Example 2 reaches 148.0 (100 Hz), and the dielectric loss is 0.14. It can be seen that the composite material prepared by the present invention achieves the technical effect of obtaining a high dielectric constant at a lower ceramic content and having a lower dielectric loss.
Claims
1. A three-dimensional porous ceramic, characterized in that: The raw materials for its preparation include: photosensitive resin and dielectric ceramic particles; The weight ratio of the photosensitive resin to the dielectric ceramic particles is 1:(1.2-4).
2. The three-dimensional porous ceramic according to claim 1, characterized in that: The dielectric ceramic particles include a first barium titanate and a second barium titanate; the particle size of the first barium titanate is 0.1-5 μm, and the particle size of the second barium titanate is 20-500 nm; Preferably, the mass ratio of the first barium titanate to the second barium titanate is 1:(2-5).
3. The three-dimensional porous ceramic according to claim 1, characterized in that: In terms of weight percentage, the raw materials for preparing the photosensitive resin include 90-95% of resin monomer, 1-5% of leveling agent, 0.5-3% of viscosity regulator, and 0.5-2% of photoinitiator.
4. The three-dimensional porous ceramic according to claim 3, characterized in that: The resin monomer includes one or more combinations of 1,6-ethylene glycol diacrylate, trimethylolpropane triacrylate, 2-methyl-2-hydroxyethyl acrylate phosphate, methyl methacrylate, ethylene glycol dimethacrylate, isobornyl acrylate, lauric acid methacrylate, and cyclotrimethylolpropane formal acrylate; Preferably, the resin monomers include 1,6-ethylene glycol diacrylate, trimethylolpropane triacrylate and 2-methyl-2-hydroxyethyl acrylate phosphate.
5. A method for preparing a three-dimensional porous ceramic according to any one of claims 1 to 4, characterized in that: The preparation steps include: S1. The photosensitive resin and dielectric ceramic particles are mixed and ball-milled to obtain a dielectric ceramic slurry; S2. 3D printing the dielectric ceramic slurry to obtain an ordered functional ceramic skeleton; S3. Surface treatment is performed on the ordered functional ceramic skeleton to obtain a three-dimensional porous ceramic product.
6. The method for preparing the three-dimensional porous ceramic according to claim 5, characterized in that: The S2 step specifically includes: S2.1 placing the dielectric ceramic slurry in a resin tank of a 3D printer and printing according to a set model to obtain a ceramic green body; S2.2 The ceramic green body is sintered once to obtain an ordered functional ceramic skeleton.
7. The method for preparing the three-dimensional porous ceramic according to claim 6, characterized in that: In step S2.1, the printing conditions are set as follows: the printing layer thickness is 10-50 μm, the single layer exposure time is 5-20 s, and the light curing energy is 2.1 mW / cm 2 .
8. The method for preparing the three-dimensional porous ceramic according to claim 6, characterized in that: In the step S2.2, the conditions for the primary sintering are set as follows: placing the ceramic green body in a muffle furnace, heating it to 1100-1500° C. at a rate of 0.5-3° C. / min, and sintering it for 2-5 hours.
9. The method for preparing the three-dimensional porous ceramic according to claim 5, characterized in that: The step S3 specifically includes: immersing the ordered functional ceramic skeleton in a polyvinyl alcohol aqueous solution, taking it out, drying it, and performing secondary sintering to obtain a three-dimensional porous ceramic product; Preferably, the temperature of the secondary sintering in step S3 is 800-950° C., and the time of the secondary sintering is 1-4 hours.
10. An application of the three-dimensional porous ceramic according to any one of claims 1 to 4, characterized in that: The three-dimensional porous ceramic is used in electronic devices, medical equipment, communication equipment, and aerospace fields.
Citation Information
Patent Citations
Structured ceramic composites modeled after natural materials and made via cold sintering
CN111032327A
A 3D printed barium titanate ceramic and preparation method thereof
CN117447198B